THE EFFECT OF WATER DISCHARGE ON THE POWER PRODUCED BY THE GENERATOR AT PLTM GUNUNG WUGUL PT. PLN INDONESIA POWER MRICA PGU 2x1,5 MW - Mei Lutfiani, Isfiani; Noor Prasetyono, Rizki; Mubarok, Rizky (Program Studi Teknik Elektro Universitas Peradaban, 2024)
The availability of fossil energy is increasingly in crisis due to its continuous use. The best alternative to anticipate this is new renewable energy (EBT). Minihydro Power Plant (PLTM) is a small-scale power plant that uses water power as the main medium to drive turbines and generators, the water comes from rivers by utilizing the height of the waterfall and the amount of water discharge. By knowing the water discharge value, it will later be analyzed with the power value produced by the generator. The type of research used is quantitative analysis research and pre-experimental one shot case study using the help of IBM SPSS Statistics 25 for Windows laptop software. Based on the results of simple linear regression analysis on summary, ANOVA and coefficient models. In the summary model, it is known that the R Square value is 1,000, which means that the influence of the independent variable (water flow) on the dependent variable (power) is 100%. And this is confirmed by the coefficient results which show a significance value of 0.000 < 0.05, which means that the water discharge has an effect on the power produced by the generator. The higher the water discharge value, the higher the power produced.